Strategies for Developing a Culture of Quality in Islamic Educational Institutions: Strategi Pengembangan Budaya Mutu Dalam Lembaga Pendidikan Islam - Aeni, Umdatul; Istikomah (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality assurance forms the primary pillar for institutional sustainability and educational excellence in Islamic academic organizations. Specific Background: Building a robust quality culture requires leadership support, strategic planning, and structural adaptation across schools, madrasahs, and boarding institutions. Knowledge Gap: However, systematic syntheses examining integrated operational dimensions of quality culture strategies specifically within Islamic educational contexts remain limited. Aims: This study synthesized prior empirical research from 2019 to 2024 to critically analyze quality culture development strategies in Islamic educational institutions using a Systematic Literature Review (SLR) guided by PRISMA guidelines. Results: The synthesis revealed five core strategy pillars: student-centered focus, total institutional involvement, measurable evaluation systems, strong leadership commitment, and continuous quality improvement. Novelty: This research establishes a unified multi-dimensional framework bridging theoretical quality management principles with practical Islamic institutional governance. Implications: Educational leaders can implement these strategy dimensions to optimize stakeholder management, institutional competitiveness, and sustained educational performance. Key Findings Highlights Five fundamental pillars—student focus, total involvement, measurement, commitment, and continuous improvement—define effective quality culture development. Professional leadership and open stakeholder communication directly strengthen institutional capacity and continuous educational adaptation. Combining internal quality assurance systems with external supervision ensures consistent standards and long-term institutional sustainability. Keywords: Quality Culture Development, Islamic Educational Institutions, Systematic Literature Review, Quality Management Strategies, Institutional Quality Improvement